Solving Environmental and Water Problems in Uzbekistan (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Let me start at once with the fact that Uzbekistan is the birthplace of ecology. This is proved by the fact that 3000 years ago our ancestors, or more precisely Khorezmians, first wrote a great book "AVESTA" (7th century BC). It is imbued with the idea: Man should always keep himself clean, protect vegetation and ensure purity of land, water and air.